The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1194/jlr.r062760
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of glycosylphosphatidylinositol anchored proteins from the endoplasmic reticulum to the cell surface

Abstract: This article is available online at http://www.jlr.org vesicular traffi cking events ( 1 ). Many secretory proteins that are delivered to the cell surface, including a wide diversity of receptors, adhesion molecules, and enzymes, are attached to the external leafl et of the plasma membrane via a glycosylphosphatidylinositol (GPI) anchor ( 2 ). The core structure of the GPI anchor precursor is largely conserved in evolution and consists of a phospholipid moiety (acylphosphatidylinositol) with a glycan backbone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 88 publications
(112 reference statements)
3
90
0
Order By: Relevance
“…As an initial clue we observed that in growing roots the localization of the F4C∆Fas1‐1 protein in endosomes was dramatically increased compared with the mostly plasma membrane localized protein full‐length F4C. Because N‐ glycosylation is involved in the apical sorting of mammalian GPI‐APs (Muniz and Riezman, ), one could speculate that the highly N‐ glycosylated Fas1‐1 domain might be required for the efficient secretion of FLA4. However, several observations argue against this interpretation.…”
Section: Discussionmentioning
confidence: 92%
“…As an initial clue we observed that in growing roots the localization of the F4C∆Fas1‐1 protein in endosomes was dramatically increased compared with the mostly plasma membrane localized protein full‐length F4C. Because N‐ glycosylation is involved in the apical sorting of mammalian GPI‐APs (Muniz and Riezman, ), one could speculate that the highly N‐ glycosylated Fas1‐1 domain might be required for the efficient secretion of FLA4. However, several observations argue against this interpretation.…”
Section: Discussionmentioning
confidence: 92%
“…Since myriocin-, FB1-, PDMP-, and D609-suppressed GlcHCers level only disrupted the subcellular localization of the GPI-anchored PD proteins and not that of PDLP1 protein, we hypothesized that the GPI-anchored PdBG2 and PDLP1 proteins might use different cargo machinery in a GlcHCers-enriched vesicle-dependent manner. The secretory pathways for GPI-anchored proteins and non GPI-anchored transmembrane or secretory proteins are distinct in yeast and mammalian cells (Funato and Riezman, 2001; Muniz et al, 2001; Watanabe et al, 2008; Castillon et al, 2009; Rivier et al, 2010; Muniz and Zurzolo, 2014; Paladino et al, 2014; Muniz and Riezman, 2016). During protein secretion in yeast, GPI-anchored proteins are segregated from other proteins and delivered to their final destination by SL-enriched vesicles (Silva et al, 2007; Kajiwara et al, 2008; Loizides-Mangold et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Of note is, however, that an assessment of the GPI-AP expression levels seems more sensitive in the fibroblasts than in blood cells [23]. This might also be related to the trafficking pathways of GPI-APs through ER and Golgi that differ for cell types and substrates [66, 67].…”
Section: Discussionmentioning
confidence: 99%